A case study of rice sheath rot disease occurence in different granary area at Tanjong Karang, Selangor / Che Nor Farhana Che Ismail - Che Ismail, Che Nor Farhana (Faculty of Plantation and Agrotechnology, 2016)
In Malaysia, rice widely planted in Peninsular Malaysia particularly in north region which includes Perlis, Kedah, Perak, Terengganu and a few areas in Selangor and south of Malaysia. Unfortunately, there are several major diseases in the paddy cultivation. These diseases have become more resistant and the farmer was getting low production lately. Among of the diseases, sheath rot is distorting disease of rice. Sheath rot disease that is caused by Sarocladium oryzae. A survey was conducted at several areas in Tanjong Karang at the early April 2016. Therefore, the objective for the present study to determine the incidence and severity of sheath rot disease in different granary areas at Tanjong Karang, Selangor and to determine the factors that influence the incidence and severity of sheath rot disease in granary areas at Tanjong Karang, Selangor. A 1m x 1m quadrant was used to measure and placed it randomly on the quadrant at three different fields in Tanjong Karang, Selangor. All the data were observed and recorded. From the three field that were surveyed, the result showed field B has the highest mean of disease incidence with 48.67% whereas severity 61.78%. Second highest mean of disease incidence was field C with 27.61% whereas severity was 58.22%. The lowest mean of disease incidence was field A with 14.06% whereas severity was 28.21 %. The occurrence of the disease probably because of amount of fertilizer used, planting method and soil pH. For the conclusion, the objective of this survey is successfully achieved.